Blastocyst-Derived Lactate as a Key Facilitator of Implantation - Kathryn H. Gurner; David K. Gardner (Biomolecules)
The blastocyst develops a unique metabolism that facilitates the creation of a specialized microenvironment at the site of implantation characterized by high levels of lactate and reduced pH. While historically perceived as a metabolic waste product, lactate serves as a signaling molecule which facilitates the invasion of surrounding tissues by cancers and promotes blood vessel formation during wound healing. However, the role of lactate in reproduction, particularly at the implantation site, is still being considered. Here, we detail the biological significance of the microenvironment created by the blastocyst at implantation, exploring the origin and significance of blastocyst-derived lactate, its functional role at the implantation site and how understanding this mediator of the maternal–fetal dialogue may help to improve implantation in assisted reproduction.